Spillover effects of clients’ tax enforcement on financial statement auditors: Evidence from a discontinuity design - CHOW, Travis K. (Institutional Knowledge at Singapore Management University, 2019)
We examine the impact of clients’ tax enforcement on financial statement auditors. In a regression discontinuity design, we exploit the firm-registration-date-based application of a new rule that assigns firms to two different tax enforcement regimes. Our analysis implies that auditors exert less effort–evident in lower audit fees and shorter audit report lags–when their clients are monitored by the more stringent tax authority. In results supporting that audit quality improves in this situation despite the fall in auditor effort, we report that clients subject to tougher tax enforcement exhibit a lower incidence of accounting restatements and tax-related restatements. Additionally, we find no evidence of impaired auditor independence evident in the informativeness of auditors’ modified opinions. Finally, we document that clients undergoing stricter tax enforcement are assigned less-experienced partners, suggesting that tax enforcement enables audit firms to optimize client-partner matching. Collectively, our research suggests that tax authority oversight engenders a positive externality by improving external audit efficiency.